Logarithmic matrix transformations into Gw - Mulatu Lemma (International Journal of Mathematics and Mathematical Sciences)
We introduced the logarithmic matrix Lt and studied it as mappings into ℓ and G in 1998 and 2000, respectively. In this paper, we study Lt as mappings into Gw.